Temperature Correction Computation System - Kasbon, Rozana (2008)
Temperature Correction Computation System is a computerized system used for estimating formation temperature captured from electric logs. The use of formation temperature evaluation analysis is important in geological basins where the possible production hole can be determined. The objectives of this project are to embed additional computation system to an existing Thermal Profile Computation System, to apply the Horner-Plot Thermal Recovery method in calculating the temperature formation of a well and to reduce the computation time of obtaining the effective temperature cooling value. The temperature cooling time is a critical input to derived formation temperature, and the effective value needs to be obtained because there are several factors, of effects, that can cause steady state measurement errors during the drilling. The formation temperature is important for geoscientist to understand the origin and evolution of sedimentary basins, oil and gas generation. The methods to gather data during the research phase are conducting regular interview with stakeholders and scrutinizing literature reviews. There are number of distinct stages involves in developing the system. The phases are planning, requirement analysis, design, development and implementation. These stages consist of phases during which the IT work procedures are defined and the product is created or modified. The system fulfilled the project’s objective to minimize the standard error percentage in comparison to manual computation. By using the system, the percentage of the standard error in obtaining a consistent temperature cooling value is 0.05%. The system also fulfilled the objective to increase the efficiency of log data computation. The vast amount of time needed to manually compute one well is significantly reduced to an efficient time of 60 seconds, and this applies to both calculation of one well log data and calculation of multiple well log data.